2023
DOI: 10.3390/w15142503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Behavior of Groundwater Storage Systems at Different Time Scales in Basins of South Central Chile: A Study Based on Flow Recession Records

Abstract: Understanding the groundwater storage and release (S-Q) process and its contribution to river flows is essential for different hydrological applications, especially in periods of water scarcity. The S-Q process can be characterized based on recession parameter b, which is the slope of the power–law relationship −dQ/dt = aQb of the recession flow analysis, where recession parameter b represents the linearity of the S-Q process. In various studies, it has been found that this parameter can present high variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This aquifer system is the source of water for many industries, municipalities, and rural water users. The major secondary aquifers consist of Silurian and Devonian carbonate rocks and Quaternary sand and gravel (Nicholas et al, 1987). Figure 9, to be discussed later in detail, shows the aquifer map of Rock River basin, while Figure 10 shows the elevation map of two major aquifers in study area.…”
Section: Catchment Detailsmentioning
confidence: 99%
“…This aquifer system is the source of water for many industries, municipalities, and rural water users. The major secondary aquifers consist of Silurian and Devonian carbonate rocks and Quaternary sand and gravel (Nicholas et al, 1987). Figure 9, to be discussed later in detail, shows the aquifer map of Rock River basin, while Figure 10 shows the elevation map of two major aquifers in study area.…”
Section: Catchment Detailsmentioning
confidence: 99%
“…Recession flow analysis is a simple and valuable tool for characterizing the dynamics of the behavior of the groundwater storage and release process of an aquifer [26][27][28][29], as it provides information on watershed functioning, related to runoff generation, storage retention, and baseflow dynamics [30]. For example, Tashie et al [31] analyzed the recession behavior of 1027 streams in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Li and Ameli [32] found that the streamflow recession behavior strongly depends on different geological, morphological, and hydrological watershed characteristics. Parra et al [28] recently analyzed recession behavior in several Chilean watersheds through moving-time-window analysis and how this behavior was related to geomorphological and climatic variability characteristics. The authors found that the recession behavior in wet periods tends toward fast drainage, while in dry periods it tends toward slow drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis and imitative approaches, such as Piper diagrams, Gibbs diagrams, Chadha diagrams, and the ionic ratio are powerful and useful tools for evaluating the chemical characteristics of groundwater and the underlying factors [19][20][21][22]. Geochemical models are valuable in computing chemical reactions occurring in groundwater systems; comprehensive processes like solid dissolution and precipitation; ion exchange; and sorption by clay minerals [23][24][25][26][27][28]. Statistical correlation analysis, which establishes connections between various physicochemical factors, holds promise for advancing groundwater quality management.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical correlation analysis, which establishes connections between various physicochemical factors, holds promise for advancing groundwater quality management. Moreover, integrated multivariate statistical approaches, such as CA and PCA, are powerful tools in identifying significant physicochemical characteristics and discerning relationships among these variables, contributing to a deeper understanding of the primary drivers influencing the distribution of physicochemical variables [15,24,29].…”
Section: Introductionmentioning
confidence: 99%